The Learning Curve, Market Dominance, and Predatory Pricing - Cabral, Luis M. B.; Riordan, Michael H. (Econometrica, 1994)
Strategic implications of the learning curve hypothesis are analyzed in the context of a price-setting, differentiated duopoly selling to a sequence of heterogeneous buyers with uncertain demands. A unique Markov perfect equilibrium is characterized and sufficient conditions are provided for market dominance to be self-reinforcing. Increasing market dominance implies that learning is privately disadvantageous. Finally, introducing avoidable fixed costs and possible exit into the model yields a new theory of predatory pricing based on the learning curve hypothesis. Copyright 1994 by The Econometric Society.